KESALAHAN BERBAHASA BIDANG MORFOLOGI DALAM BERITA ONLINE MAJALAHLARISE.COM RUBRIK PENDIDIKAN - Avika Dara Fortuna; Sri Muryati; Sukarno Sukarno (Universitas Batanghari, 2023)
This study aims to describe and correct the location of language errors in the morphology field in its affixation which is published from online news namely Larise.com Magazine. The focus of this research is on describing aspects of language errors in morphology, especially in affixation. Sampling of data sources was carried out purposively and snowballing, and the collection technique was using download, reading, and note-taking techniques. The data analysis technique used the agih method. The results of the research will be described systematically, factually, and accurately regarding language errors in morphology in the online news Magazinelarise.com. The data was collected and then analyzed whether there were errors in the use of words in the writing of the online news. After that, they were totaled and grouped based on the morphological process of their affixation. The data of this research is the form of error words that are written in the news and the data sources are collected from 10 online news in the education rubric of the June-December 2021 edition. This research is a descriptive qualitative research. In this study, the researcher focuses more on the affixation section which includes: prefixation, infixation, suffixation, confix, and simulfix. The results of this study contained 10 educational rubrics above, the results of this study contained 9 language errors with 5 types of morphological affixation including 2 prefixation errors, namely the addition of prefixes (meN-) and (ber-), 3 suffixation errors including the addition of suffixes ( -an) and Foreign (-al), 1 infixation error, namely the addition of infixation (-in-), 3 affix combination errors, namely the addition of confixes (ber-kan), (di-kan), and (meN-i), and 1 Simufik's error is the addition of simulfixation (pen-kan).